Bias-corrected estimates of reduction of post-surgery length of stay and corresponding cost savings through the widespread national implementation of fast-tracking after liver transplantation: a quasi-experimental study. (3rd July 2019) - Loh, Chung-Ping A.; Croome, Kristopher P.; Burcin Taner, C.; Keaveny, Andrew P.
Abstract: Background: Fast-tracking is an approach adopted by Mayo Clinic in Florida's (MCF) liver transplant (LT) program, which consists of early tracheal extubation and transfer of patients to surgical ward, eliminating a stay in the intensive care unit in select patients. Since adopting this approach in 2002, MCF has successfully fast-tracked 54.3% of patients undergoing LT. Objectives: This study evaluated the reduction in post-operative length of stay (LOS) that resulted from the fast-tracking protocol and assessed the potential cost saving in the case of nationwide implementation. Methods: A propensity score for fast-tracking was generated based on MCF liver transplant databases during 2011–2013. Various propensity score matching algorithms were used to form control groups from the United Network of Organ Sharing Standard Analysis and Research (STAR) file that had comparable demographic characteristics and health status to the treatment group identified in MCF. Multiple regression and matching estimators were employed for evaluation of the post-surgery LOS. The algorithm generated from the analysis was also applied to the STAR data to determine the proportion of patients in the US who could potentially be candidates for fast-tracking, and the potential savings. Results: The effect of the fast-tracking on the post-transplant LOS was estimated at approximately from 2.5 ( p -value = 0.001) to 3.2 ( p -value < 0.001) days based on various matching algorithms. The cost saving from a nationwide implementation of fast-tracking of liver transplant patients was estimated to be at least $78 million during the 2-year period. Conclusion: The fast-track program was found to be effective in reducing post-transplant LOS, although the reduction appeared to be less than previously reported. Nationwide implementation of fast-tracking could result in substantial cost savings without compromising the patient outcome.